Impact of Sowing Dates on the Growth and Yield Performance of Modern Wheat Varieties Under the Argo-Climatic Conditions of D.I. Khan - Khan, Rashid; Khan, Haris (Journal of Cross-Disciplinary Sustainability Innovations, 2025)
A field experiment was conducted to assess the impact of different sowing dates on the growth and yield of various wheat varieties under irrigated conditions at the Agronomic Research Area, Gomal University, Dera Ismail Khan, during 2013. The study was arranged in a Randomized Complete Block Design (RCBD) with a split-plot layout and three replications. Sowing was done manually using a hand-driven drill. The net plot measured 1.8m × 5m, comprising six rows, each 5m long and spaced 30cm apart. Factor A represented sowing dates, while Factor B included different wheat varieties. The findings indicated significant effects of both sowing dates and wheat varieties on growth and yield parameters. The most favorable results were obtained from the October 25 sowing, which recorded the highest values for days to heading (101.25), spike length (9.45 cm), tiller density (316.94 m²), biological yield (11.58 t ha⁻¹), grain yield (6.29 t ha⁻¹), and grain filling duration (79.75 days). In contrast, wheat sown on December 5 produced lower yield parameters. Among the tested varieties, Pirsabak-13 achieved the highest grain yield (6.29 t ha⁻¹) when sown on October 25, followed by Hashim-8 (6.42 t ha⁻¹) when sown on November 15. Gomal-8 yielded the lowest grain output (3.43 t ha⁻¹) when planted on December 5. Based on these results, it is recommended that wheat cultivation in Dera Ismail Khan should be conducted between October 25 and November 15, with Pirsabak-13 being the most suitable variety for early sowing, while Hashim-8 and Gomal-8 should be grown at their optimal sowing times.